2010
DOI: 10.1002/adfm.201000025
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2‐(dimethylamino)ethyl methacrylate) Brushes with Incorporated Nanoparticles as a SERS Active Sensing Layer

Abstract: A simple, fast, and versatile approach to the fabrication of outstanding surface enhanced Raman spectroscopy (SERS) substrates by exploiting the optical properties of the Ag nanoparticles and functional as well as organizational characteristics of the polymer brushes is reported. First, poly(2‐(dimethylamino)ethyl methacrylate) brushes are synthesized directly on glassy carbon by self‐initiated photografting and photopolymerization and thoroughly characterized in terms of their thickness, wettability, morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 53 publications
7
80
0
Order By: Relevance
“…22 Among them, the use of host−guest interaction allows the arrangement of metal NPs to the polymers with good stability and controllable uniform size, and a lot of studies have been reported about the host−guest interaction between noble metal NPs and polymers. 19,23−26 Cyclodextrin capped NPs is favored for its facile preparation, which are usually used to fabricate supramolecular aggregates by self-assembly of CD capped NPs and polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Among them, the use of host−guest interaction allows the arrangement of metal NPs to the polymers with good stability and controllable uniform size, and a lot of studies have been reported about the host−guest interaction between noble metal NPs and polymers. 19,23−26 Cyclodextrin capped NPs is favored for its facile preparation, which are usually used to fabricate supramolecular aggregates by self-assembly of CD capped NPs and polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22 Among them, the use of host−guest interaction allows the arrangement of metal NPs to the polymers with…”
Section: ■ Introductionmentioning
confidence: 99%
“…40 °C, at which the transmittance drops abruptly. [ 3 ] Above the LCST, the size of PDMAEMA-g -PDA microcapsules is slightly smaller than the size below the LCST. The differences can be attributed to the hydrophobic PDMAEMA, which improves the hydrophilicity of the microenvironment surrounding the microcapsule particles.…”
Section: Resultsmentioning
confidence: 98%
“…As this Raman peak have no adverse impacts to the SERS signal of analytes, PDMS could be a feasible supporting material for SERS substrates. In order to quantitatively study the SERS enhancement ability of the AgNL/PDMS substrates, the enhancement factors (EF) were estimated according to the equation EF = (I SERS /I NR )(C NR /C SERS ) [24,25]. Normal Raman signals of R6G (1×10 −2 mol L −1 ) were obtained using the same hemispherical dimple without SERS substrate and the EFs were calculated at the main peaks of 1361, and 1648 cm −1 (SI, S6).…”
Section: Resultsmentioning
confidence: 99%